2014
DOI: 10.1002/ajim.22324
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and current pesticide exposure among Latino farmworkers in comparison to other Latino immigrants

Abstract: Background Pesticide exposure poses a health risk for farmworkers. This analysis documents lifetime and current pesticide exposure of North Carolina Latino migrant farmworkers, with comparison to non-farmworker Latino immigrants. Methods During May–October 2012, 235 Latino farmworkers and 212 Latino non-farmworkers completed interviews with items to construct measures of lifetime, current residential and occupational pesticide exposure. Results Farmworkers experience levels of lifetime and residential pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…27 The results establish that our intended differences in pesticide exposure between the groups are reflected in their reports of work and living environments. 28 Genetic variability may affect cholinesterase activities, 29 as well as pesticide metabolism. 30 While measuring such variability was beyond the scope of this study, we included only individuals of Hispanic heritage from North, Central, or South America to try to reduce this unmeasured variability.…”
Section: Discussionmentioning
confidence: 99%
“…27 The results establish that our intended differences in pesticide exposure between the groups are reflected in their reports of work and living environments. 28 Genetic variability may affect cholinesterase activities, 29 as well as pesticide metabolism. 30 While measuring such variability was beyond the scope of this study, we included only individuals of Hispanic heritage from North, Central, or South America to try to reduce this unmeasured variability.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous analysis has shown that the two groups do represent very different exposure histories. (40) Further, our approach is the basis of the Agricultural Health Study, which has provided extension information on the association of pesticide exposure and neurologic outcomes among farmers. (14)…”
Section: Discussionmentioning
confidence: 99%
“…(40) All participants were men aged 30 to 70 who self-identified as Latino or Hispanic; almost all spoke Spanish as their primary language. Farmworkers had to be currently employed as agricultural laborers and to have worked in agriculture for at least three years.…”
Section: Methodsmentioning
confidence: 99%
“…Data were obtained from the Preventing Agricultural Chemical Exposure 4 (PACE4) project (see ref 21 for more details), a community-based participatory research collaboration between the NC Farmworkers Project (Benson, NC), El Buen Pastor Latino Community Services (Winston-Salem, NC), and Wake Forest School of Medicine (Winston-Salem, NC). Farmworkers were recruited from three agricultural counties in east-central NC (Harnett, Johnston, Sampson), and non-farmworkers were recruited from an urban area in central NC (Winston-Salem, Forsyth County).…”
Section: Methodsmentioning
confidence: 99%
“… Note that comparisons between occupational groups were done using two sample t tests, and that significant differences between groups are highlighted with bold text. 1 Data on years of occupational pesticide exposure are from Arcury et al 21 . …”
Section: Figurementioning
confidence: 99%